Protective effects of quercetin against hyperglycemia-induced oxidative stress in hepatic HepG2 cell line - Amir Yarahmadi; Mostafa Moradi Sarabi; Ahmad Sayahi; Fatemeh Zal (Mashhad University of Medical Sciences, 2021)
Objective: Hyperglycemia is a severe consequence of diabetes mellitus (DM). Throughinduction of oxidative stress, it plays a major role in the pathogenesis of several complications in DM. Therefore, new strategies and antioxidants should be implemented inthe treatment of DM. Quercetin is a flavonoid with strong antioxidant capacity found dominantly in vegetables, fruits, leaves, and grains. The current study aimed to investigate quercetin protective effects under D-glucose-induced oxidative stress by assessing antioxidant defense enzymes inHepG2 cells as an in vitro model. Materials and Methods: HepG2 cells were cultured with different concentrations of D-glucose (5.5, 30 and 50 mM) and/or 25 μM quercetin for 48 and 72 hr, respectively. The effect of treatments on cellular integrity, antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR) activity, andcellular levels of glutathione (GSH) and malondialdehyde (MDA) wasdetermined. Results: D-glucose had various effects on intracellular antioxidant defense atdifferent doses and time-points and quercetin could attenuate oxidative stress and modulate antioxidant defenses. Conclusion: The results of this study indicated that flavonoid quercetin could be proposed as an agent protecting hepatic HepG2 cells against oxidative stress associated with hyperglycemia.